(untitled) (Applied Biological Research, 2014)
The present investigation was undertaken to identify suitable cultivars for commercial grain production for human consumption on the basis of nature of inter-relationship between β-glucan, grain quality and yield. The experimental material comprised of ten oats (Avena sativa L.) genotypes which were evaluated under temperate conditions of Kashmir for chlorophyll content, leaf area index, grain protein content, β-glucan content and grain yield. The highest chlorophyll content and leaf area index was recorded in genotype SKO-211 and highest grain protein in genotype SKO-209. The highest β-glucan and grain yield was achieved in genotype SKO-208. Correlation studies on the degree of interrelationship between various parameters revealed that grain yield exhibited a significant positive genotypic correlation with chlorophyll content, leaf area index and β-glucan. From the study it appears oats genotypes viz., SKO-208, SKO-209 and SKO-207 may be suitable for commercial grain production for human consumption on the basis desirable grain quality characteristics and grain yield but these genotypes need further testing under different environments.